(untitled) (Indian Journal of Animal Production and Management, 2024)
The study was under taken for assessment of shelter management of dairy cows in and around the greater Guwahati city of Assam. Total 173 numbers of farmers were randomly selected from the specified areas and divided into two categories viz. farmers having crossbred cattle (F1) and farmers with only local cattle (F2). The crossbred cattle were reared in intensive and local cattle were in semi-intensive system of feeding. The long axis of sheds was 35.84, 26.59, 23.70 and 13.87 percent in the north-south, east-west, north-west and south-west orientations, respectively. Thatched roofs were 75.72 percent followed by 19.65 and 4.62 percent corrugated G.I. and asbestos sheeted, respectively. There was highly significant (p<0.01) difference between F1 and F2 farmers in respect of prevailing roofing materials. The highest 58.96 percent of the cattle sheds were made of earthen floor followed by 37.57 and 3.47 percent brick bedded and concrete, respectively. There was highly significant (p<0.01) difference between the categories of farmer in respect of types of floor. The average floor space (excluding manger) per cow was 1.90±0.04 and 2.05±0.03 sq. meters in case of F1 and F2 types of farmers, respectively. There was highly significant (p<0.01) difference between the farmers for average floor space. The average height at eaves was 1.65±0.04 and 1.70±0.04 meters in F1 and F2, respectively. The gutter and manger was used by F1 farmers only. The width and length per cow of common manger was 1.25±0.02 and 1.00±0.01 meter, respectively. The manger was made of bamboo and woods (91.18%) and concrete (8.82%). The average depth and width of gutter was 0.15±0.003 and 0.35±0.004 meter, respectively. The gutters (88.24%) were made of brick.